2001
DOI: 10.1055/s-2001-15180
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin, Norepinephrine and Dopamine Involvement in the Antidepressant Action of Hypericum Perforatum

Abstract: Hypericum perforatum is considered an effective alternative to the synthetic antidepressants in the treatment of mild-to-moderate depression. Recently, we showed that the effects on neurotransmitter contents in different brain regions of laboratory animals are more evident after administration of hypericum extracts containing a higher concentration of flavonoids, thus suggesting that these compounds are important in the antidepressant action of hypericum perforatum. We studied the effects of Ph-50, a hypericum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…A mouse was judged to be immobile when it remained floating in water, making only the necessary movements to keep its head above water. Each mouse was only tested once (Calapai et al, 2001). Increase in the duration of immobility was considered to reflect a depressant-like effect of the drug.…”
Section: Forced Swimming Test (Fst)mentioning
confidence: 99%
“…A mouse was judged to be immobile when it remained floating in water, making only the necessary movements to keep its head above water. Each mouse was only tested once (Calapai et al, 2001). Increase in the duration of immobility was considered to reflect a depressant-like effect of the drug.…”
Section: Forced Swimming Test (Fst)mentioning
confidence: 99%
“…Other authors have demonstrated that H. perforatum can block dopamine reuptake by presynaptic neurons (Calapai et al, 2001;Menini, Gobbi, 2004). This mechanism could explain the reduced number of rotations seen on the 7 th day, but not on the 14 th and 21 st days after lesion, since the H. perforatum administration was only performed until the 7 th post-lesion day.…”
Section: Resultsmentioning
confidence: 92%
“…Studies showed that substances responsible for the activity of alcoholic St. John's wort extract are hyperforin and hypericin. These substances inhibit the reuptake of neurotransmitters such as serotonin and noradrenaline [23][24][25]. Additionally, many studies confirmed the effect of St. John's wort on the expression level of P-gp and CYP3A4.…”
Section: Influence Of Herbal Materials On P-glycoprotein Expressionmentioning
confidence: 95%